Modern canonical quantum general relativity - Thiemann, Thomas (Cambridge University, 2013)
This book provides a complete treatise of the canonical quantization of general relativity. The focus is on detailing the conceptual and mathematical-framework, describing the physical applications; and summarizing the status of this program in its most popular incarnation: Joop quantum gravity. Mathematical concepts and their relevance to physics are provided within this book, so it is suitable for graduate-students and researchers with a basic knowledge of quantum field theory and general relativity.